Farmers' Social Capital in Supporting Sustainable Agriculture: The Case of Pujon Kidul Tourism Village, Indonesia - Achmad Tjachja Nugraha; Rahmawati, Rahmawati; Auliah, Aidha; Gunawan Prayitno (Fakultas Teknik Universitas Brawijaya, 2022)
Pujon Kidul Village is a village with the potential of the main agricultural sector which has been designated and developed into a Pujon Kidul Tourism Village. Tourism villages that are developed need support within the village itself to maintain sustainability. Tourist villages that do not pay attention to the sustainability aspect will threaten the social and economic conditions of the community, especially the farming community, who make up most rural communities. Therefore, it is necessary to support sustainable agriculture that can balance sustainable tourism. The most important capital that must be prepared to achieve sustainable agriculture is social capital from the farming community. Social capital is the main force to empower communities in development, this study examines how the conditions and factors are forming the social capital of the farming community of Pujon Kidul tourism village. This study's main data collection method used a questionnaire aimed at 221 respondents. Then the questionnaire results will be described and analyzed by CFA analysis. Overall, the social capital of the farming community is in good condition, and this is a potential that can be used in determining the right approach to the farming community of Pujon Kidul Tourism Village in supporting sustainable agriculture